Cultivation and conservation in Ngorongoro conservation area, Tanzania - Boone, Randall B.; Galvin, K.A.; Thornton, Philip K.; Swift, D.M.; Coughenour, M.B. (Springer, 2006)
Ngorongoro Conservation Area (NCA), Tanzania, contains renowned wildlife, an expanding human population, and cultivation by Maasai agro-pastoralists and non-Maasai agriculturalists. We used integrated assessments to explore some effects of cultivation on livestock, resident wildlife, and people. Using a Landsat image from 2000, we mapped 3,967 ha [9,803 acres (ac)] of cultivation within NCA, or 39.7 km2 of the 8,283 km2 conservation area. Using integrative ecosystem (Savanna) and household (PHEWS) models, we assessed effects of: up to 50,000 ac (20,234 ha) of cultivation; cultivation concentrated into two blocks totaling 10,000 ac (4,047 ha) and 20,000 ac (8,094 ha) that may be more palatable to tourists; and human population growth. Simulations with from 10,000 to 50,000 ac in cultivation showed no large changes in ungulate populations relative to there being no cultivation. When cultivation was altered to be in two blocks, some wildlife populations changed (=15%) and ungulate biomass remained the same. When cultivation was increased linearly with human population, poor households needed 25% of their diets to come from relief as populations tripled, because livestock could not increase significantly. Our results indicate that having <1% of NCA in cultivation, in its current distribution, is not overly detrimental to wildlife or livestock populations, and is important to Maasai well-being.